Expression of acidic fibroblast growth factor cDNA confers growth advantage and tumorigenesis to Swiss 3T3 cells. - Jaye, M (1988)
Acidic fibroblast growth factor (aFGF), a polypeptide with a mol. wt of approximately 16,000, is a potent mitogen for a variety of cells and shares 55% amino acid sequence identity with basic FGF. The recent isolation of three new oncogenes which share 35-45% amino acid sequence similarity with the FGFs suggests that the coding sequences for the FGFs themselves may be oncogenic under certain circumstances. To test this hypothesis, we cotransfected 3T3 NR6 cells with factors expressing the aFGF coding sequence and the bacterial neomycin gene. The aFGF produced by cotransfected cells was found only in the cellular homogenate and not in medium conditioned by the cells. Cells expressing aFGF grew to 10 times the density of control cells at saturation and were multilayered and disorganized, similar to transformed cells. The cotransfected cells do not grow in soft agar, but show enhanced soft agar growth relative to controls in the presence of added aFGF and heparin. The aFGF-producing cells formed small, non-progressive tumors when injected subcutaneously into nude mice. Our data suggest that expression of aFGF in NR6 cells results in enhanced growth, and that several traits characteristic of the transformed phenotype are partially expressed.